PERANAN GURU DALAM MENGHADAPI PENGARUH NEGATIF PENGGUNAAN INTERNET - Harry Dhika; Fitriana Destiawati; Aulia Paramita (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
The introduction of the internet to children from an early age is one of the factors that will affect the progress of a nation in the future, however with the development of technology there will be both positive and negative impacts. In this study, the socialization of the role of early childhood teachers in dealing with the negative effects of internet use on children aims to provide convenience in using technology, especially the internet, on children's development. The results of this study are to provide an understanding of the positive and negative impacts of internet use on early childhood students, knowing its implementation is expected to provide ease in using current technology.